Morphological traits and root anchorage ability of native pioneer tree species for reforestation of mudstone badlands. Issue 4 (4th July 2022) - Lee, Jung-Tai; Lin, Yu-Syuan; Shi, Cheng-Ying; Lee, Ming-Jen
ABSTRACT: Mudstone badlands occupy a large area in southwestern Taiwan. Mudstone soils with poor cementation property are particularly vulnerable to water erosion and landslides during rainy seasons. Broussonetia papyrifera, Hibiscus taiwanensis and Macaranga tanarius are major pioneer tree species occurring on mudstone badlands. Therefore, these species are beneficial for slope stabilization and forest restoration to control erosion and landslide. Nevertheless, information on their morphological traits and root biomechanical properties are lacking. In this research, root morphological traits of these species were inspected utilizing WinRHIZOPro Image Analysis System. Root anchorage ability and root tensile strength of 1-year-old B. papyrifera, H. taiwanensis and M. tanarius saplings were evaluated using uprooting testing and root tensile testing. The results show, compared to H. taiwanensis, B. papyrifera and M. tanarius plants had markedly greater root traits. Moreover, the root anchorage abilities of M. tanarius and B. papyrifer plants were notably higher than that of H. taiwanensis. In addition, root tensile strength of M. tanarius plants was markedly higher than those of B. papyrifera and H. taiwanensis plants. The results clearly demonstrate that M. tanarius outperforms B. papyrifera and H. taiwanensis, in these traits. Taken together, the priority for selecting these species for reforestation of mudstone badlands follows as: M. tanarius > B. papyrifera > H. taiwanensis. These results, together with the information on ecological succession following erosion and landslide, allow us to develop the reforestation plan and management strategy of mudstone badlands.